Relações Raciais e Questão Social: contradições dialeticamente racializadas e radicalizadas - um improrrogável debate ao Serviço Social - Rodrigues, Cheliman Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The research has as main objective to investigate the space occupied by the discus-sion that emphasizes the racial issue as an essential element in its genesis and perpetuation of the social issue especially in the Brazilian context, in the training in Social Work. It recognizes that the social issue constitutes the object of work of so-cial workers and, therefore, must be understood in its entirety. In addition, the study argues that structural racism plays a fundamental role in maintaining the social is-sue in Brazil and that this social issue in Brazil is even more radicalized because it is racialized, being present in its foundations and manifestations. The research adopts a qualitative approach and uses both field research and literature review to deepen the discussion. In the field research component, the study involves a dia-logue with four Social Work professors, who, through semi-structured interviews, share their perceptions about the relationship between the social issue and the ra-cial issue in the training of new social workers. The fundamental objective is to en-rich the reflections on the interconnection between ethnic-racial issues and the so-cial issue, as well as to evaluate the relevance of this debate in the training of social workers

A pesquisa tem como principal objetivo investigar o espaço ocupado pela discussão que enfatiza a questão racial como um elemento essencial na gênese e perpetuação da questão social especialmente no contexto brasileiro, na formação em Serviço Social. Ela reconhece que a questão social constitui o objeto de trabalho dos (as) assistentes sociais e, portanto, deve ser compreendida em sua totalidade. Além disso, o estudo argumenta que o racismo estrutural desempenha um papel fundamental na manutenção da questão social no Brasil e que essa questão social no Brasil é ainda mais radicalizada por ser racializada, estando presente em seus fundamentos e manifestações. A pesquisa adota uma abordagem qualitativa e utiliza tanto pesquisa de campo quanto revisão bibliográfica para aprofundar a discussão. No componente de pesquisa de campo, o estudo envolve um diálogo com quatro docentes de Serviço Social, que, por meio de entrevistas semiestruturadas, compartilham suas percepções sobre a relação entre a questão social e a questão racial na formação de novos assistentes sociais. O objetivo fundamental é enriquecer as reflexões sobre a interconexão entre as questões étnico-raciais e a questão social, bem como avaliar a relevância desse debate na formação dos (as) assistentes sociais.
Racial relations and the social question: dialectically racialized and radicalized contradictions - an unavoidable debate in Social Work
Keywords: Racismo Estrutural; Questão social; Serviço Social; Structural racism; Social issue; Social Work